Adaptive multimedia content delivery for contextaware u-learning. (1st January 2011) - Zhao, Xinyou; Okamoto, Toshio
Empowered by mobile computing, teachers and students can benefit from computing in more scenarios beyond the traditional computer classroom. But because of the much diversity of device specification, learning contents and mobile context existing today, the learners get a bad learning experience (e.g. rich contents cannot be displayed correctly) during ubiquitous learning (u-learning) environment. This paper proposes an adaptive contents delivery model for context-aware u-learning according to three-level service models proposed, which create the adaptive contents for learners to get a seamless access in learning according to learners' interest and contexts. The evaluation on a mobile virtual community system shows that the learners may not only study in rich media on mobile device at anytime and at anyplace, also get a better learning experience, e.g. learners may get instant help from other participates by ubiquitous device and access the rich contents: PowerPoint files.